SISTEM PENYIRAMAN TANAMAN MENGGUNAKAN ALGORITMA FUZZY LOGIC BERBASIS INTERNET OF THINGS DENGAN ENERGI SURYA - Mohammad Fajar Maulidi; Tanhella Zein Vitadiar (JUTIM (Jurnal Teknik Informatika Musirawas), 2026)
Irregular watering of plants often leads to water waste and reduced plant growth quality. This study developed an IoT-based automatic watering system using a Fuzzy Logic algorithm powered by solar energy and equipped with a buzzer as a warning for critical conditions. A soil moisture sensor is used to read soil moisture, while a DHT11 sensor monitors environmental temperature. Sensor data is processed by an ESP32 microcontroller to determine automatic watering decisions, and the results are displayed through the Blynk application so users can monitor the system in real-time. Tests on corn plants showed that the system is able to turn on the water pump only when needed and save water usage compared to manual watering. The addition of a buzzer effectively provides notification when humidity is very dry. This system is proven to be efficient, energy independent, and supports the concept of smart and sustainable agriculture.